2016
DOI: 10.1038/srep24398
|View full text |Cite
|
Sign up to set email alerts
|

Have GRACE satellites overestimated groundwater depletion in the Northwest India Aquifer?

Abstract: The Northwest India Aquifer (NWIA) has been shown to have the highest groundwater depletion (GWD) rate globally, threatening crop production and sustainability of groundwater resources. Gravity Recovery and Climate Experiment (GRACE) satellites have been emerging as a powerful tool to evaluate GWD with ancillary data. Accurate GWD estimation is, however, challenging because of uncertainties in GRACE data processing. We evaluated GWD rates over the NWIA using a variety of approaches, including newly developed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(128 citation statements)
references
References 43 publications
4
124
0
Order By: Relevance
“…Therefore, when surface water storage change (in soil and snow) is known, the groundwater can be obtained after subtracting the GLDAS surface total water storage from the total water storage change derived by GRACE (Jin & Feng, ; M. Rodell, Velicogna, & Famiglietti, ). Previous studies found a good agreement between GRACE‐estimated and in situ‐observed groundwater variations (Feng et al, ; Chen et al, ; Xiao et al, ; Long et al, ). The equation can be expressed as italicΔW=italicΔitalicGW+italicΔitalicSM+italicΔitalicSWE, …”
Section: Methodssupporting
confidence: 53%
“…Therefore, when surface water storage change (in soil and snow) is known, the groundwater can be obtained after subtracting the GLDAS surface total water storage from the total water storage change derived by GRACE (Jin & Feng, ; M. Rodell, Velicogna, & Famiglietti, ). Previous studies found a good agreement between GRACE‐estimated and in situ‐observed groundwater variations (Feng et al, ; Chen et al, ; Xiao et al, ; Long et al, ). The equation can be expressed as italicΔW=italicΔitalicGW+italicΔitalicSM+italicΔitalicSWE, …”
Section: Methodssupporting
confidence: 53%
“…Intercomparison of different products has been recently carried out by Farinotti et al () and shows the large potential of these new datasets to work at scales closer to the groundwater management scale (scales ∼ 100,000 km 2 ). For details on GRACE TWS processing to extract GWS contribution, associated uncertainties linked to GRACE large‐scale sensitivity (truncation, filtering, and leakage), and estimation of storage compartments (Equation ), the interested reader can refer to Longuevergne et al (), Scanlon et al (), and Long et al ().…”
Section: Detection Of Groundwater Depletionmentioning
confidence: 99%
“…This may result in the inaccurate GWS and the associated error estimate as the uncertainties in observation and of the land surface model outputs are neglected in the combination (or regression) of two noisy data (e.g. Long et al, 2016). In data assimilation, the GRACE uncertainty is often derived empirically, not necessarily reflecting the actual GRACE error characteristics (e.g.…”
Section: Introductionmentioning
confidence: 99%